1998
DOI: 10.1136/sti.74.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Auxotypes, serovars, and trends of antimicrobial resistance of Neisseria gonorrhoeae in Kigali, Rwanda (1985-93)

Abstract: Objective: To investigate the in vitro antimicrobial susceptibility and the auxotype/serovar distribution of Neisseria gonorrhoeae in Kigali, Rwanda, during 1985-93. Methods: As part of a monitoring programme the in vitro susceptibility of 1604 isolates of N gonorrhoeae was determined by agar dilution. Auxo-and serotyping was performed on 1350 and 1313 isolates respectively. Results: The prevalence of penicillinase producing N gonorrhoeae (PPNG) remained stable at a rate of 39% during 1985-91 and increased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…[6][7][8][9] Data from the late 1980s and 1990s from Rwanda indicate the presence of multidrug resistance among various pathogens including Streptococcus pneumoniae, Neisseria gonorrhea, Salmonella typhimurium, and Shigella species. [10][11][12][13][14] Subsequent reports by Muvunyi and others in 2011, showed higher rates of AMR than previously reported among uropathogenic Escherichia coli isolates, suggesting increasing trends for AMR. 15 Quite alarming in that study was the observed high rate of resistance of E. coli to commonly used oral antibiotics to treat urinary tract infections, including amoxicillin (89.3%), ciprofloxacin (41.3%), nitrofurantoin (44.9%), and cotrimoxazole (82.7%).…”
Section: Introductionmentioning
confidence: 78%
“…[6][7][8][9] Data from the late 1980s and 1990s from Rwanda indicate the presence of multidrug resistance among various pathogens including Streptococcus pneumoniae, Neisseria gonorrhea, Salmonella typhimurium, and Shigella species. [10][11][12][13][14] Subsequent reports by Muvunyi and others in 2011, showed higher rates of AMR than previously reported among uropathogenic Escherichia coli isolates, suggesting increasing trends for AMR. 15 Quite alarming in that study was the observed high rate of resistance of E. coli to commonly used oral antibiotics to treat urinary tract infections, including amoxicillin (89.3%), ciprofloxacin (41.3%), nitrofurantoin (44.9%), and cotrimoxazole (82.7%).…”
Section: Introductionmentioning
confidence: 78%
“…In this study, as well as in all African studies, using recommended methods, all GC isolates were fully susceptible to third generation cephalosporins and to spectinomycin 5,6,8,10,18,19,22,23 . In many African countries, N. gonorrhoeae in vitro susceptibility to thiamphenicol or chloramphenicol has decreased continuously during the last decade 6,11,23,24 . In 2 recent studies no resistance to thiamphenicol/ chloramphenicol was observed 7,19 .…”
Section: Discussionmentioning
confidence: 95%
“…Our results for kanamycin are in agreement with all African studies using recommended methods and correct in vitro resistance breakpoints 6 with results from studies using non recommended methods which showed resistance prevalences of 17± 23% 25,26 . For TMP± SMZ, African studies using recommended techniques detected resistance levels of 0± 6%, where studies that used non recommended techniques detected resistance levels of 14% to >90% 6,7,19,20,23,26 .…”
Section: Discussionmentioning
confidence: 97%